2000
DOI: 10.1007/s100380070036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel polymorphisms in the AXIN1 and CDX-2 genes

Abstract: Axin and Cdx-2 play important roles in the tumorigenesis of human liver and colon. We have identified seven novel single-nucleotide polymorphisms (SNPs) in the AXIN1 gene and three in the CDX-2 gene. The identification of SNPs in these cancer-associated genes establishes a basis for future investigations to detect losses of heterozygosity in tumors; these SNPs may also provide genetic background information associated with cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…We confirmed three previously published single-nucleotide polymorphisms (SNPs) (Lin et al, 2000;Dahmen et al, 2001). One polymorphism resulted in an amino-acid substitution, and the others were silent SNPs.…”
Section: Mutation Of the Axin1 Gene In Oesophageal Sccsupporting
confidence: 90%
“…We confirmed three previously published single-nucleotide polymorphisms (SNPs) (Lin et al, 2000;Dahmen et al, 2001). One polymorphism resulted in an amino-acid substitution, and the others were silent SNPs.…”
Section: Mutation Of the Axin1 Gene In Oesophageal Sccsupporting
confidence: 90%
“…We screened 35 endometrial carcinomas for AXIN1 mutations in which either b-or g-catenin nuclear expression had been detected and did not find any mutations in AXIN1 but observed 12 single-nucleotide polymorphisms (SNPs). SNPs, with and without aminoacid changes, have been described in exons 1, 4, 5, 9 and 10 and intron 4 of the AXIN1 gene (Lin et al, 2000;Webster et al, 2000). Liu et al (2000) reported that AXIN2 was mutated in 11 out of 45 colorectal carcinomas with MSI, but in none out of 60 tumours without MSI.…”
Section: Discussionmentioning
confidence: 99%
“…The entire coding sequence, including the exon–intron boundaries, was investigated by PCR-SSCP using the previously described 23 sets of primers with slight modifications (Lin et al , 2000). All amplifications were performed in 15  μ l PCR containing 50–100 ng DNA, 1.5 m MgCl 2 , 0.02 m dATP, 0.2 m dGTP, dCTP and dTTP each, 0.8  μ Ci of [ 32 P]dATP (Amersham Biosciences, Buckinghamshire, UK), 20 pmol of each primer and 0.3 U AmpliTaq Gold polymerase (Perkin-Elmer Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%